2004
DOI: 10.1152/ajpheart.00568.2004
|View full text |Cite
|
Sign up to set email alerts
|

Novel targets of ANG II regulation in mouse heart identified by serial analysis of gene expression

Abstract: Schwartz, Faina, Arvi Duka, Irena Duka, Jing Cui, and Haralambos Gavras. Novel targets of ANG II regulation in mouse heart identified by serial analysis of gene expression. Am J Physiol Heart Circ Physiol 287: H1957-H1966, 2004. First published July 8, 2004 doi:10.1152/ajpheart.00568.2004.-Although the central role of ANG II in cardiovascular homeostasis is well appreciated, the molecular circuitry of its many actions is not completely understood. With the use of serial analysis of gene expression to assess g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 56 publications
(68 reference statements)
1
16
0
Order By: Relevance
“…These results are consistent with recent reports of Cx43 downregulation and dephosphorylation in heart failure (1, 2). ANG II is known to affect transcription of multiple genes (45), possibly explaining the mRNA changes. Nevertheless, the origin of the chamberspecific regulation of connexins is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with recent reports of Cx43 downregulation and dephosphorylation in heart failure (1, 2). ANG II is known to affect transcription of multiple genes (45), possibly explaining the mRNA changes. Nevertheless, the origin of the chamberspecific regulation of connexins is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…62 More recently, we have found that Ang II in vivo and in vitro stimulates gene overexpression of various vasoactive factors, including the B 1 R and B 2 R genes 53 as well as a novel gene, the cardiomyopathy-associated 3, also known as myomaxin and recently renamed Xirp2. [63][64][65] Although this gene's product remains unknown, its contribution to ischemic cardiomyopathy is crucial, as shown by studies in genetically engineered mice. 65 Interestingly, concurrent inhibition of the AT 1 receptor of Ang II with losartan can abolish the BK receptor upregulation.…”
Section: B 2 R-mediated Cardioprotection Post Ischemic Injurymentioning
confidence: 99%
“…In the heart, it acts in both endocrine and paracrine fashions to regulate contractility, impulse propagation, remodeling, growth, and apoptosis [12]. Ang II has two major receptor subtypes, the AT 1 -R and the AT 2 -R, where CM are the major sites for these receptors expression [14,15]. The AT 1 -R mediates the classical functions of Ang II in the heart tissue, such as vasoconstriction and blood pressure elevation, mainly through the stimulation of phospholipase C, the mobilization of Ca 2+ and the phosphorylation of MAPK [15].…”
Section: Introductionmentioning
confidence: 99%
“…Ang II has two major receptor subtypes, the AT 1 -R and the AT 2 -R, where CM are the major sites for these receptors expression [14,15]. The AT 1 -R mediates the classical functions of Ang II in the heart tissue, such as vasoconstriction and blood pressure elevation, mainly through the stimulation of phospholipase C, the mobilization of Ca 2+ and the phosphorylation of MAPK [15]. The AT 2 -R seems to act as a sustainable repressor of AT 1 -R signaling pathway [14,16].…”
Section: Introductionmentioning
confidence: 99%